Critical Thinking Analysis of Students in Problem Based Mathematics Learning through TBLA - Siti Maghfirotun Nikmah; Nur Fauziyah; Syaiful Huda (JME (Journal of Mathematics Education), 2021)
Mathematics is related to numbers and formulas, as well as its abstract nature. So that understanding it is not by memorizing. It requires the ability to solve mathematical problems. In solving mathematical problems it requires critical thinking skills. Problem-based learning is the right way to train students to think critically, so problem-based learning according to the purpose of improving critical thinking. To find out problem-based learning is able to improve students' critical thinking skills, the Transcript Based Lesson Analysis (TBLA) learning analysis method is used. This research is an exploratory qualitative research that aims to describe critical thinking and tendencies in problem-based mathematics learning using TBLA for students in class VIII-D at SMP Negeri 1 Gresik. The supporting instrumens in this study consisted of documentation using an audio-visual recording device and sheets for lesson analysis the TBLA model.  From the results of the TBLA analysis, both based on the number of letters and categorization, it can be seen that problem-based mathematics learning tends to be dominated by students. In the results of the TBLA analysis based on the number of letters, it appears that students are active in communicating with other students, only occasionally asking the teacher about things that need more explanation. Likewise, the results of the TBLA analysis based on categorization show that students have critical thinking skills, namely students can show 6 critical thinking indicators in this study, namely focus, reason, inference, situation, clarity and overview.